MARKETING STRATEGY OF SPONSORSHIP IN SPORT - Nebojša Maksimović; Radenko Matić; Svetlana Mihić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
The paper outlines the preparation of sponsorship offer in sport. Analitically, each phase in preparation for sponsorship offer has been analised step by step as well as all necessary actions that marketing team undertakes during the realisation and when the sponsorship program is finished.